Integration of Pancasila Student Profiles in Project-Based Mathematics Learning - Wahyuni, Nur (PT. Anagata Sembagi Education, 2025)
The integration of the Pancasila Student Profile into mathematics learning is a strategic effort to foster character while improving students' academic competence. This study aims to describe the application of the Pancasila Student Profile values in project-based mathematics learning in the school environment. The method used is descriptive qualitative with data collection techniques through observation, documentation, and interviews with teachers and students. The results of the study indicate that values such as mutual cooperation, critical reasoning, and independence can be internalized effectively through contextual and collaborative mathematics project activities. Project-based learning not only strengthens the understanding of mathematical concepts but also shapes students' attitudes and behaviors in accordance with the Pancasila Student Profile. These findings recommend the need to strengthen the role of teachers in designing integrative and student-centered learning projects.